Evaluation of the preventive effectiveness of influenza vaccines in St. Petersburg - M. K. Erofeeva; M. A. Stukova; E. V. Shakhlanskaya; Zh. V. Buzitskaya; V. L. Maksakova; T. I. Krainova; T. M. Chirkina; M. M. Pisareva; D. A. Lioznov (Эпидемиология и вакцинопрофилактика)
Background. The influenza vaccination coverage has steadily increased in the Russian Federation. The introduction of new domestic influenza vaccines into practice and the study of their effectiveness are of great importance for public health. However, a systematic analysis of the effectiveness of vaccines manufactured and used in Russia in recent years has not been performed. The aim ofthe study was to assess the epidemiological effectiveness of three domestic influenza vaccines in St. Petersburg during the 2018–2019 epidemic season.Material and methods. The organized community of 1892 young students aged 18 to 23 years has been under supervision during the period of time from October 2018 to March 2019. Influenza vaccines Grippol Plus, Sovigripp, and Ultrix were used for vaccination.Results and discussion. Prophylactic vaccination with influenza vaccines Sovigripp, Grippol Plus and Ultrix in the fall of 2018 led to a decrease in the incidence of influenza and other acute respiratory infections (ARI) by a total of 1.6–3.8 times; a decrease in the incidence of influenza by 2.7–7.1 times; the total protective efficacy of vaccines against influenza and ARI was 52.4%, and against influenza, taking into account laboratory correction, 73.3%.Conclusions. Under the conditions of the viruses circulating in Russia and in St. Petersburg in the 2018–2019 epidemic season the strains introduced into the composition of influenza vaccines, domestic influenza vaccines were characterized by good tolerance, were safe, areactogenic and had a pronounced protective effect. If the viruses circulating in Russia and in St. Petersburg in the 2018–2019 epidemic season corresponded to the strains introduced into the composition of influenza vaccines, domestic influenza vaccines, showing good tolerance, safety and low reactogenicity, had a pronounced protective effect.